The Influence of Education Level and Employment Absorption on Poverty with Unemployment Rate as An Intervening Variable in Cirebon Regency 2011-2023 - Ummah, Gabriel Rosyidatul; Bakhri, Syaeful; Fatmasari, Dewi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This study aims to analyze the impact of education level and labor absorption on the poverty rate, with the unemployment rate as an intervening variable in Cirebon Regency, using data from 2011 to 2023. The method used in this research is a quantitative analysis method with path analysis. The data type used is secondary data obtained from the Central Bureau of Statistics of Cirebon Regency, including data on education levels, labor absorption (the number of employed people), unemployment, and poverty rates from 2011 to 2023. Data processing in this study uses IBM SPSS version 25 software. The results of this study indicate no significant effect of education level on the unemployment rate, a negative and significant impact of labor absorption on the unemployment rate, a significant effect of education level on the poverty rate, a negative and significant impact of labor absorption on the poverty rate, no significant effect of the unemployment rate on the poverty rate, and that the unemployment rate is not an intervening variable between education level and the poverty rate. Still, it is an intervening variable between labor absorption and the poverty rate.